2012
DOI: 10.1089/thy.2011-0521
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and Levothyroxine-responsive Liver Dysfunction in a Patient with Ring Chromosome 18 Syndrome

Abstract: Background: Ring chromosome 18 [r(18)] is a rare constitutional chromosomal aberration syndrome, characterized by dysmorphic face, hypoactivity, short stature, and delayed development. Autoimmune thyroiditis and immunoglobulin (Ig) A deficiency are occasionally associated with chromosome-18 deletion syndromes. Summary: Here, we report a 2-year-old male child with r(18) syndrome and a selective IgA deficiency ( < 1.6 mg/ dL, reference range [rr]: 20-149), who developed hypothyroidism and liver dysfunction. Thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This finding is consistent with the previous studies done by other investigators [7][8][9][10] . Mean serum ALT level in a hypothyroid case was found significantly greater in comparison to euthyroid value in a study done by Ohkubo et al 7 . In this study researchers reported a case of a 2-year-old male child with ring chromosome 18 who developed hypothyroidism and liver dysfunction.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with the previous studies done by other investigators [7][8][9][10] . Mean serum ALT level in a hypothyroid case was found significantly greater in comparison to euthyroid value in a study done by Ohkubo et al 7 . In this study researchers reported a case of a 2-year-old male child with ring chromosome 18 who developed hypothyroidism and liver dysfunction.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, autoimmune manifestations are also common in these patients [37,39], suggesting a common genetic/pathophysiological link. Five recent case reports reinforce this notion, wherein IgAD in patients with the above chromosome aberrations were shown to be concomitant with Graves' disease [40][41][42][43], SLE [41], T1D [40] and JRA [44].…”
Section: Key Pointsmentioning
confidence: 90%